The Role of Transportation in the Countries of Fragmented Shape: Japan as an Example - Aidan, Ali Salman; Abdul Hayali, Abdul Amir Abbas (Journal of Tikrit University for Humanities, 2023)
Japan is one of the countries with a fragmented or scattered shape, which is one of the worst forms from the view point of researchers in geopolitics, because of the difficulties in the field of transport and in the military field and it causes many obstacles that stand as an obstacle in building the power of the state. Japan has been able to overcome these obstacles through variables of technology, where it was able to solve the problem of transportation through the development of transport and communications technological sector as it comes at the forefront of countries in this field. As for the problem of the military field, it has been able to develop its military capabilities very significantly, which made it the fifth rank in the world in the field of military spending, quantity and quality of weapons, as well as the quantity of the armed forces. It has been able to manufacture and import effective and advanced defensive and quality weapons.